Identifying Context-Specific Categories for Visualizing Livability of Cities—a Case Study of Malmö - Kyoko Takahashi; Shogo Kudo; Norikazu Furukawa; Doreen Ingosan Allasiw; Eigo Tateishi; Joakim Nordqvist (Challenges in Sustainability, 2018)
Livability is a concept being applied to cities, even though it is vague. Worldwide, there are several livable city ranking schemes in use, which compare the livability of cities by making use of standardized indicator sets. The research presented here recognizes, as a point of departure, that each city is unique, implying that comparisons of cities by standardized categories only does not adequately reflect the reality of each city. A qualitative approach to identify context-specific categories of livability is proposed and employed to the case of Malmo ̈ in Sweden. Through interviews, nine context-specific categories were identified and visualized. The findings of the study demonstrate that a qualitative approach enables a more in-depth description of livability categories because it can capture and illustrate relationships among the categories. An explicit awareness of such relationships may provide a more holistic perspective to city officials and planners as they aim to improve the livability of their cities. The study concludes that a qualitative approach in identifying context-specific categories can complement existing assessment schemes and allow a better grasp of livability challenges to cities.